Identifikasi Penyakit Yang Disebabkan Oleh Jamur Dan Intensitas Serangannya Pada Tanaman Cabai (Capsicum annum l.) di Kebun Percobaan Fakultas Pertanian Universitas Riau - Sri Sulastri; Muhammad Ali; Fifi Puspita (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
Chili production in Riau can not meet the needs of the community, because production is still low. One cause of low production of chili in Riau is the infection of disease. The disease is often found in pepper plant caused by the fungus Colletotrichum sp, Cercospora sp . Symptoms and the intensity of the disease are different. So it is necessary to identify the symptoms, causes of disease, the description and the level of disease to be able to control the disease. Identification was carried out at the experimental farm unit in Faculty of Agriculture University of Riau. This study aims to identify the symptoms, causes of disease, the description and the level of disease. The study was conducted using a survey method. Determination of the location of chili crop land is by purposive sampling. Sampling was conducted by a diagonal method with a random sampling of 5 points. The result showed that the disease on pepper plants in the experimental farm unit of the faculty of agriculture University of Riau is cercospora leaf spot disease caused by Cercospora sp (40%), fruit roots and Spot anthracnose twigs caused by Colletotrichum sp (25% and 22,5%). Keyword: Chili, identification of disease and intensity of disease.